On the Language of Weather Forecasts - Josipović, Višnja (Array, 1986)
The author points to some specific features of the language of weather forecasts in British daily papers on the stylistic, syntactic and lexical levels. These are: conciseness, manifested by ellipsis and, in this connection, the tendency towards lexicalization, rather than grammaticalization ; and, in many respects, interesting syntax and vocabulary.